The influence of locus of control and financial technology payment on financial management behavior with financial self-efficacy as an moderating variable among MSMEs in Malang City - Ramadani, Suci Kurnia; Mardiana (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2025)
This research aims to analyze the influence of locus of control and financial technology payment on financial management behavior with financial self-efficacy as a moderating variable among MSMEs in Malang City. The research method used is associative quantitative with a Partial Least Square (PLS) approach using SmartPLS 3.0. The research results show that locus of control and financial technology payments have a positive and significant effect on financial management behavior. Apart from that, financial self-efficacy as a moderating variable has a significant influence in strengthening the relationship between financial technology payments and financial management behavior but does not have a significant influence in strengthening the relationship between locus of control and financial management behavior. These findings support the theories of Social Learning Theory and Social Cognitive Theory, which emphasize the importance of individual confidence in controlling finances and the use of financial technology in improving better financial behavior. Therefore, it is recommended for MSME players to increase financial literacy and utilize financial technology to support the sustainability of their businesses.